A general solution to the maximum detachment force in thin film peeling. (1st May 2022) - Yin, Hanbin; Peng, Zhilong; Yao, Yin; Chen, Shaohua; Gao, Huajian
Abstract: While it is well known that the steady-state detachment force during 90° peeling of an elastic film on a rigid substrate provides a simple and powerful method to determine the interfacial work of adhesion, the situation is less clear for the maximum detachment force associated with the peeling process. Here, we propose a general solution to this maximum detachment force during 90° peeling, which is shown to depend on the interfacial work of adhesion, interfacial strength, bending modulus of the film, as well as an interfacial cohesive law shape factor. Combining this solution with Kendall's classical model provides a method that allows the interfacial work of adhesion and interfacial strength of a film-substrate system to be simultaneously determined via peeling test.